Niacin exacerbates β cell lipotoxicity in diet-induced obesity mice through upregulation of GPR109A and PPARγ2: Inhibition by incretin drugs - Zhang, Xiaojing; Zhu, Baoyi; Lin, Peibin; Liu, Xiaoping; Gao, Jun; Yin, Dazhong; Zeng, Jianwen; Liao, Baojian; Kang, Zhanfang (Frontiers in Endocrinology, 2022)
The widely used lipid-lowering drug niacin was reported to increase blood glucose in diabetes. How does niacin regulate β Cell function in diabetic patients remains unclear. This study aimed to investigate the effect of niacin on β cell lipotoxicity in vitro and in vivo. Niacin treatment sensitized the palmitate-induced cytotoxicity and apoptosis in INS-1 cells. In addition, palmitate significantly increased the niacin receptor GPR109A and PPARγ2 levels, which could be further boosted by niacin co-treatment, creating a vicious cycle. In contrast, knocking down of GPR109A could reverse both PPARγ2 expression and niacin toxicity in the INS-1 cells. Interestingly, we found that GLP-1 receptor agonist exendin-4 showed similar inhibitive effects on the GPR109A/PPARγ2 axis and was able to reverse niacin induced lipotoxicity in INS-1 cells. In diet-induced obesity (DIO) mouse model, niacin treatment resulted in elevated blood glucose, impaired glucose tolerance and insulin secretion, accompanied by the change of islets morphology and the decrease of β cell mass. The combination of niacin and DPP-4 inhibitor sitagliptin can improve glucose tolerance, insulin secretion and islet morphology and β cell mass, even better than sitagliptin alone. Our results show that niacin increased β cell lipotoxicity partially through upregulation of GPR109A and PPARγ2, which can be alleviated by incretin drugs. We provide a new mechanism of niacin toxicity, and suggest that the combination of niacin and incretin may have better blood glucose and lipid control effect in clinical practice.